Organic salt composition of pressure sensitive adhesives produced by spiders - Wolff, Jonas O.; Cherry, Brian R.; Yarger, Jeffery L.; Adler, Lewis; Thomas, Donald S.; Hook, James M.; Blamires, Sean J. (Frontiers in Ecology and Evolution, 2023)
Natural glues offer great potential as bio-inspired solutions to problems associated with the performance of synthetic adhesives. Spider viscous glues are elastic pressure sensitive adhesives (PSAs) that physically adhere to surfaces on contact across a range of environmental conditions. Extracting useful components from these secretions remains a challenge that can be met by the comparative analyses of functional analogues. Here we used 1H NMR spectroscopy and mass spectrometry to ascertain the organic salt compositions of the PSAs of four different species of Australian spiders belonging to two lineages that independently acquired aqueous gluey secretions: the St Andrew’s cross (Argiope keyserlingi), the redback (Latrodectus hasselti), the false widow (Steatoda grossa), and the daddy long-legs spider (Pholcus phalangiodes). The PSAs from each of these spiders contained similar organic salts, albeit in variable concentrations. The adhesives of the false widow and daddy long-legs spider had mixtures of only a few components, of which betaine predominated, while the PSAs of the other spiders predominantly contained small organic acids such as GABA/GABA-amide, isethionate, and choline salts. Our results suggest that the PSA composition of spiders is likely to be influenced more by environmental factors than evolutionary history and are guided by common principles. Our findings could be valuable for facilitating the design of more sustainable synthetic glues.